IbPTK PENUMBUHAN WIRAUSAHA BARU BERBASIS TECHNOPRENEURSHIP DI INKUBATOR BISNIS - Adi, R. Kunto; Riptanti, Erlyna Wida; Irianto, Heru (INOTEKS: Jurnal Inovasi Ilmu Pengetahuan,Teknologi, dan Seni, 2016)
This community service generally aims to increase the capacity of Incubator Bussiness Unit PSP - KUMKM and SME tenants so as to improve the students' technoprenership skill. The first year program was aimed at: (1) establishing the productivity of Business Incubator Unit based on the marketing point, the local potention and ease of technology; (2) strengthening the management of the productive unit.The establishment of this business unit starting from the selection of candidates tenants who have high motivation and willingness effort. The three people chosen werefrom the alumni of D3 Agribusiness and Technology Agricultural Production.Jackfruit, salak, pineapple and apple were choosen to be processed into chips. The results already achieved in the first year were: (1) the productive business unit at Business Incubator was established; (2) management of Food Industry Household licenses (PI-RT) was in the process; (3) the fruit chips began the production on a regular basis with a daily production capacity reached 5 kg; (4) interlacement business partnerships with some relevant stakeholders have been conducted